Judaism in late antiquity. - Neusner, Jacob, 1932-; Avery-Peck, Alan J. 1953-; Chilton, Bruce. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2000)
What, in Judaism - a religion so concerned with social norms and public policy - can we possibly mean by \'law\'? That is the thoroughly fresh perspective with which this work commences. It proceeds with two chapters on Second Temple Judaism, and two on the special subject of the Dead Sea library. Learning withers when criticism is substituted by political consensus, and when other than broadly accepted viewpoints find a hearing only with difficulty, if at all. The editors, therefore, invited colleagues from the USA, Europe, and the State of Israel to systematically outline their views in one account and set it alongside contrary ones. The several participants explain how, in broad and sweeping terms, they see the state of learning in their areas of special interest. The volume provides first an overview, followed by a systematic, critical account of the fading consensus. In a number of accounts, the different perspectives are presented in scholarly debate. *** Because of the willingness of contending parties to meet one another in a single frame of discourse, the work is able to portray with considerable breadth the presently contending viewpoints concerning the use of Rabbinical literature for historical purposes. *** Besides this sustained and vigorous debate, precipitated by historical-critical reading of the rabbinical literature, other issues have attracted attention, such as, for example, feminist interests.